Study of nonstandard auto-antibodies as prognostic markers in auto immune hepatitis in children - Mahmoud Nermine H; Youssef Azza M; El- Din Elshazly Lerine B; Ibrahim Mona M (BMC, 2009)
Abstract Background Antibodies to chromatin and soluble liver antigen have been associated with severe form of autoimmune hepatitis and/or poor treatment response and may provide guidance in defining subsets of patients with different disease behaviors. The major clinical limitation of these antibodies is their lower individual occurrence in patients with autoimmune hepatitis. Aim To estimate the value of detection of these non-standard antibodies in autoimmune hepatitis as prognostic markers. Methods Both antibodies were tested by enzyme immunoassay in 20 patients with autoimmune hepatitis. Results Antibodies to soluble liver antigen were not detected in any of our patients. On the other hand anti chromatin antibodies were present in 50% (10/20). Antibodies to chromatin occurred more commonly in females than males (8/14 versus 2/6). Of the 14 patients who relapsed 8(57%) had antichromatin antibodies while they were present in only 2 out of 6(33.3%) non relapsers. Antichromatin antibodies were found more in patients with antinuclear (3/4) and anti smooth muscle antibodies (9/13) more than in those with liver kidney microsomal antibodies (1/4) and those seronegative (1/4) i.e. they were +ve in patients with type I (8/12(66.6%)) more than those with type II (1/4(25%)) and those seronegative (1/4(25%)). Antibodies to chromatin are associated with high levels of γ globulin but yet with no statistical difference between seropositive and seronegative counterparts (p = 0.65). Conclusion Antibodies to chromatin may be superior than those to soluble liver antigen in predicting relapse and may be useful as prognostic marker. Further studies with larger number of patients and combined testing of more than one antibody will improve the performance parameters of these antibodies and define optimal testing conditions for them before they can be incorporated into management algorithms that project prognosis.